Prevalence of Thalassemia Among Children Aged 0 to 15 Years in Africa from 2007 to 2025: A Systematic Review and Meta-Analysis - Habibatou, Ide Amadou; Ounoussa, Tapha; Zaratou, Ali; Nadakou, N’Kpingou Theodore; Oumou, Hamidou; Aminata, Mamane Daouda; Doudou, Zeinabou Alhassane; Abdoulaye, Ousmane; Boutchi, Mounkaila (European Scientific Journal, ESJ, 2025)
Thalassemia is a genetic blood disorder that reduces hemoglobin production, leading to anemia and related complications. Thalassemia is widespread in Africa due to factors like historical malaria prevalence, migrations, and genetic factors. In Africa, there are few studies on thalassemia, leading to confusion with sickle cell disease because of a lack of diagnostic tools. Thalassemia remains a major public health issue in the region. This meta-analysis aimed to provide an update on the prevalence of thalassemia in Africa from 2007 to 2025. A systematic literature search was conducted across the PubMed, AJOL, and Google Scholar databases to identify studies published between 2007 and 2025, using specific inclusion and exclusion criteria. Quality assessment was performed using the Mixed Methods Appraisal Tool (MMAT) for prevalence studies. The heterogeneity of the included studies was assessed using the I2 and Q statistics. Funnel plots and Egger tests were performed to determine publication bias in this meta-analysis. The pooled 95% confidence interval (95% CI) prevalence of thalassemia across studies was determined using a generic random-effects inverse-variance method. Eleven studies involving 26025 children, including 2889 cases of thalassemia, were included. Prevalence rates were pooled using random-effects models due to high observed heterogeneity (I2 > 75.0%, p-value < 0.05). The overall prevalence of thalassemia was 13.4% (95% CI 8.5-19.1%, I2 = 99.1%). Subgroup analyses showed that the pooled prevalence of thalassemia was 14.0% (95% CI, 0-33%; I² = 98.5%) in newborns, 22.0% (95% CI, 11-33%; I² = 98.8%) in patients ≤ 5 years of age and 6.0% (95% CI, 3.0-9.0%; I² = 82.6%) in patients over 5 years of age. The prevalence of alpha-thalassemia carriers was 18% (95% CI, 7-28%; I² = 99.2%) and beta-thalassemia 9% (95% CI, 6-12%; I² = 98.6%). This meta-analysis revealed a high prevalence of thalassemia among children aged 0 to 15 years in Africa. The study underscores the importance of screening programs, public awareness campaigns, and genetic counseling services to address thalassemia in Africa. Policy recommendations include implementing national screening programs and increasing healthcare resources to improve early detection and management of thalassemia.